2019
DOI: 10.3390/bs9100107
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on the Impact of First Steps—A Peer-led Educational Intervention for People Newly Diagnosed with Parkinson’s Disease

Abstract: Aim: The dual aim of this research was to consider the impact of providing the First Steps program on the stories of people with Parkinson’s Disease (PD) and to investigate the psychosocial and emotional mechanisms which may explain this impact. Methods: A qualitative study using a subtle realist paradigm and hermeneutic phenomenological methodology was undertaken. A single semi-structured interview was used to consider the impact and experiences of people with PD who completed either the intervention (2-day p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…The results showed no significant improvements in self‐rated depression or quality of life at post‐intervention. A recent qualitative study (Soundy et al, 2019) explored the experiences of people with PD who underwent First Steps, a 2‐day peer‐led psychoeducational intervention for people with a new diagnosis of PD. The results showed that the participants engaged well with the programme, showing improved exercise behaviour and coping mechanisms at post‐intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed no significant improvements in self‐rated depression or quality of life at post‐intervention. A recent qualitative study (Soundy et al, 2019) explored the experiences of people with PD who underwent First Steps, a 2‐day peer‐led psychoeducational intervention for people with a new diagnosis of PD. The results showed that the participants engaged well with the programme, showing improved exercise behaviour and coping mechanisms at post‐intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Further research is required to consider the impact of the intervention on mood states, as changes have been identified across other chronic illnesses [ 23 ]. Additionally, consideration is needed around the impact of how close the diagnosis was or how severe the symptoms were as these aspects may be important in identifying if and how changes occur [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…La EP es la segunda causa más común de enfermedad neurodegenerativa después de la enfermedad de Alzheimer (22,23) ; de progreso lento e invalidante tanto física, cognitiva y socialmente, afecta aproximadamente al 0,3% de la población, incrementándose hasta el 3% en mayores de 65 años (22,23) . La progresión y severidad de la EP es variable entre los pacientes (24).…”
Section: Discussionunclassified